Zoonotic Tick-Borne Pathogens in Temperate and Cold Regions of Europe—A Review on the Prevalence in Domestic Animals - Springer, Andrea; Glass, Antje; Topp, Anna-Katharina; Strube, Christina (Frontiers in Veterinary Science, 2020)
Ticks transmit a variety of pathogens affecting both human and animal health. In temperate and cold regions of Europe (Western, Central, Eastern and Northern Europe), the most relevant zoonotic tick-borne pathogens are tick-borne encephalitis virus (TBEV), Borrelia spp. and Anaplasma phagocytophilum. More rarely, Rickettsia spp., Neoehrlichia mikurensis and zoonotic Babesia spp. are identified as a cause of human disease. Domestic animals may also be clinically affected by these pathogens, and, furthermore, can be regarded as sentinel hosts for their occurrence in a certain area, or even play a role as reservoirs or amplifying hosts. For example, viraemic ruminants may transmit TBEV to humans via raw milk products. This review summarizes the role of domestic animals, including ruminants, horses, dogs and cats, in the ecology of TBEV, Borrelia spp., A. phagocytophilum, Rickettsia spp., N. mikurensis and zoonotic Babesia species. It gives an overview on the (sero-)prevalence of these infectious agents in domestic animals in temperate/cold regions of Europe, based on 148 individual studies. Meta-analyses of seroprevalence in asymptomatic animals estimated overall seroprevalences of 2.7% for TBEV, 12.9% for Borrelia burgdorferi sensu lato (s.l.), 16.2% for A. phagocytophilum and 7.4% for Babesia divergens, with a high level of heterogeneity. Subgroup analyses with regard to animal species, diagnostic test, geographical region and decade of sampling were mostly non-significant, with the exception of significantly lower B. burgdorferi s.l. seroprevalences in dogs than in horses and cattle. More surveillance studies employing highly sensitive and specific test methods and including hitherto non-investigated regions are needed to determine if and how a changing world impacts the frequency of zoonotic tick-borne pathogens in domestic animals.